Analisis Deiksis dalam Novel Drama Vendetta Karya Intanera - Binti Shofiyah; Farida Yufarlina Rosita; Berlian Pancarrani (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to analyze the forms and functions of deixis in the novel Drama Vendetta by Intanera. The focus of the research includes five types of deixis: personal, spatial (place), temporal (time), social, and discourse deixis. Personal deixis is used to reveal the identities of characters and the relationships between speaker and listener within the narrative. Spatial deixis indicates locations that are emotionally and narratively significant to the characters, while temporal deixis reflects shifts between past, present, and future that shape the story’s emotional and structural flow. Social deixis highlights status differences, emotional distance, and levels of formality in character interactions. Meanwhile, discourse deixis serves to maintain cohesion and continuity within the text by referring to elements mentioned elsewhere in the narrative. This research employs a qualitative descriptive method with data collected through reading and note-taking techniques. The findings show that Intanera uses various types of deixis strategically to enrich narrative structure, express psychological conflict, and establish social relationships and emotional meaning throughout the novel. This study is expected to contribute to the fields of pragmatic linguistics and discourse analysis in literary texts.